Theoretical Background on Valuation Methods of Intangible Assets in Listed and Unlisted Companies: A bibliometric analysis from 2010-2024 - Alina BUTNARU (CIOBOTAR) (Communications of International Proceedings, 2024)
The study is oriented to observe the theoretical issues regarding the perception of intangible assets in listed and unlisted firms. The market, cost or income approaches are the main techniques for the valuation of intangibles in listed and unlisted firms, and the influencing factors of this process include: corprorate governance policies, the profitability of the firm or ownership structure. The bibliometric analysis showed that the number of papers dealing with the valuation of intangibles in listed firms is much higher than in unlisted firms, due to the fact that listed firms provide more complex data due to the mandatory disclosure of financial statements. It is possible that unlisted firms, although an important link in the global economy, consider the financial effort to be too great to meet the listing requirements. It should be noted that a correct evaluation of intangible resources can lead to more efficient management and investment targeting that can generate major future benefits. The study is also a signal of the growing importance of the contribution of intangibles to the total value of firms, and the need for a regulatory framework for the valuation of intangible assets should ensure a minimum degree of comparability, transparency and reasoned delineation.
Keywords: valuation; intangible assets; listed companies; unlisted